Metabolic engineering of Pseudomonas putida for production of vanillylamine from lignin‐derived substrates. Issue 6 (3rd February 2021) - Manfrão‐Netto, João Heitor Colombelli; Lund, Fredrik; Muratovska, Nina; Larsson, Elin M.; Parachin, Nádia Skorupa; Carlquist, Magnus
Summary: Whole‐cell bioconversion of technical lignins using Pseudomonas putida strains overexpressing amine transaminases (ATAs) has the potential to become an eco‐efficient route to produce phenolic amines. Here, a novel cell growth‐based screening method to evaluate the in vivo activity of recombinant ATAs towards vanillylamine in P. putida KT2440 was developed. It allowed the identification of the native enzyme Pp‐SpuC‐II and ATA from Chromobacterium violaceum ( Cv‐ATA ) as highly active towards vanillylamine in vivo . Overexpression of Pp‐SpuC‐II and Cv‐ATA in the strain GN442ΔPP_2426, previously engineered for reduced vanillin assimilation, resulted in 94‐ and 92‐fold increased specific transaminase activity, respectively. Whole‐cell bioconversion of vanillin yielded 0.70 ± 0.20 mM and 0.92 ± 0.30 mM vanillylamine, for Pp‐SpuC‐II and Cv‐ATA, respectively. Still, amine production was limited by a substantial re‐assimilation of the product and formation of the by‐products vanillic acid and vanillyl alcohol. Concomitant overexpression of Cv‐ATA and alanine dehydrogenase from Bacillus subtilis increased the production of vanillylamine with ammonium as the only nitrogen source and a reduction in the amount of amine product re‐assimilation. Identification and deletion of additional native genes encoding oxidoreductases acting on vanillin are crucial engineering targets for further improvement. Abstract : In this study, Pseudomonas putida was engineered for whole‐cell conversion of ferulic acid and vanillin to vanillylamine with ammonium as nitrogen source. Furthermore, a novel growth‐based screening method to select for recombinant vanillin transaminases was developed and used to identify SpuC‐II and Cv‐ATA as suitable enzymes for in vivo biocatalysis with P. putida .